Project management maturity & organizational reputation: a case study of public sector organizations - Muhammad Irfan; Hassan, Mazlan; Hassan, Nasruddin; Muhammad Habib; Khan, Salma; Nasruddin, Abdul Muhaimin (IEEE, 2020)
Reputation of the public sector organizations has been in the limelight of research since the last few years. It is because a positive reputation attracts foreign direct investment, elevates the trust of the general public in their government, increases the net tax collections and in aggregate improves the image and identity of the country. The aim of the present study is to propose and evaluate a research model that includes project management maturity as an antecedent to organizational reputation. The suggested research model is assessed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Furthermore, the hypotheses generated in the study were examined based on a sample of 425 respondents from the project-based public sector organizations of Pakistan. Moreover, the findings indicate that there is a significant positive relationship between maturity in project management and reputation of public sector organizations. Additionally, it is determined from the findings of the study that different dimensions of project management maturity such as process management, project management training, knowledge management transfer, continuous improvement and the use of project management software positively affect the reputation of the public sector organizations in Pakistan.